Sub PPM Detection of NO2 Using Strontium Doped Bismuth Ferrite Nanostructures - David John Dmonte; Aman Bhardwaj; Michael Wilhelm; Thomas Fischer; Ivo Kuřitka; Sanjay Mathur (Micromachines, 2023)
The present work investigates the NO2 sensing properties of acceptor-doped ferrite perovskite nanostructures. The Sr-doped BiFeO3 nanostructures were synthesized by a salt precursor-based modified pechini method and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). The synthesized materials were drop coated to fabricate chemoresistive gas sensors, delivering a maximum sensitivity of 5.2 towards 2 ppm NO2 at 260 °C. The recorded values of response and recovery time are 95 s and 280 s, respectively. The sensor based on Bi0.8Sr0.2FeO3–δ (BSFO) that was operated was shown to have a LOD (limit of detection) as low as 200 ppb. The sensor proved to be promising for repeatability and selectivity measurements, indicating that the Sr doping Bismuth ferrite could be a potentially competitive material for sensing applications. A relevant gas-sensing mechanism is also proposed based on the surface adsorption and reaction behavior of the material.